PENGARUH PENGGUNAAN HANDPHONE TERHADAP INTERAKSI SOSIAL TEMAN SEBAYA SISWA SMA 2 SUNGAI RAYA - Sumiati, Sumiati; Rustiyarso, Rustiyarso; Fatmawati, Fatmawati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe use of mobile phones in schools, besides having an effect on learning outcomes, mobile phones tend to have an influence on peer interactions at school. As a result of carrying the cellphone students are busier and more concerned with their cellphones than interacting with fellow friends around them. Students play more mobile phones like chatting with friends in their cellphone contacts. then the main problem in this study is